2012
DOI: 10.2147/ijn.s33398
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced absorption of hydroxysafflor yellow A using a self-double-emulsifying drug delivery system: in vitro and in vivo studies

Abstract: Hydroxysafflor yellow A (HSYA), the main active ingredient of the safflower plant (Carthamus tinctorius L.), is a hydrophilic drug with low oral bioavailability. Water-in-oil-in-water (w/o/w) double emulsions may enhance the oral absorption of HSYA. In this study, we prepared a selfdouble-emulsifying drug delivery system (SDEDDS) to improve the absorption of HSYA. SDEDDS consists of water in oil emulsions and hydrophilic surfactants that can self-emulsify into w/o/w double emulsions in the aqueous gastrointest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The study demonstrated that SDEDDS significantly improved the permeability of HSYA through Caco-2 cells monolayers, and plasma concentration increased by 2.17 times. The apparent permeability coefficient (Papp) of HSYA and HSYA-SDEDDS were (3.52 ± 1.41) × 10 −6 cm/s and (6.62 ± 2.61) × 10 −6 cm/s at the same concentrate (0.4 mg/ml), which improved to 1.88-fold by SDEDDS (Lv et al, 2012).…”
Section: Microemulsionsmentioning
confidence: 94%
“…The study demonstrated that SDEDDS significantly improved the permeability of HSYA through Caco-2 cells monolayers, and plasma concentration increased by 2.17 times. The apparent permeability coefficient (Papp) of HSYA and HSYA-SDEDDS were (3.52 ± 1.41) × 10 −6 cm/s and (6.62 ± 2.61) × 10 −6 cm/s at the same concentrate (0.4 mg/ml), which improved to 1.88-fold by SDEDDS (Lv et al, 2012).…”
Section: Microemulsionsmentioning
confidence: 94%
“…Some oral delivery systems of HSYA are shown in Figure 3 . They are water-in-oil microemulsion [ 65 ], self-double-emulsifying [ 66 ], hydrophobic nanoparticles [ 67 ], chitosan complex [ 68 ], solid lipid nanoparticles [ 69 ], and natural deep eutectic solvents [ 70 ].…”
Section: Pharmacokinetic Progressionsmentioning
confidence: 99%
“…Some oral delivery systems of HSYA are shown in Figure 3. They are water-in-oil microemulsion [65], self-double-emulsifying [66], hydrophobic nanoparticles [67], chitosan complex [68], solid lipid nanoparticles [69], and natural deep eutectic solvents [70]. Related research suggested that shell nanoparticles are a highly effective delivery system for resveratrol, another natural compound, due to their significant effects in increasing the bioavailability and anti-inflammation activity [71].…”
Section: Pharmacokinetics Of Oral Administrationmentioning
confidence: 99%
“…However, among many administration routes, oral administration is of great significance in drug formation because of its convenience and safety. Thus, the microemulsion, nanoemulsion, and nanoparticles of HSYA have been developed to overcome the low oral bioavailability (Li et al, 2010;Qi et al, 2011;Lv et al, 2012;Shi et al, 2018;Zhao B. X. et al, 2018). Considering the weak ability of HSYA to penetrate the BBB in physiologic condition (He et al, 2008), Borneolum Syntheticum and Acori Talarinowii Rhizoma were used to enhance its BBB permeability (Wu et al, 2011).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%